2017
DOI: 10.1111/tpj.13760
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a non‐stereoselective cytochrome P450 catalyzing either 8α‐ or 8β‐hydroxylation of germacrene A acid from the Chinese medicinal plant, Inula hupehensis

Abstract: These authors contributed equally to this work. SUMMARYSesquiterpene lactones (STLs) are C15 terpenoid natural products with a-methylene c-lactone moiety. A large proportion of STLs in Asteraceae species is derived from the central precursor germacrene A acid (GAA). Formation of the lactone rings depends on the regio-(C6 or C8) and stereoselective (a-or b-)hydroxylations of GAA, producing STLs with four distinct stereo-configurations (12,6a-, 12,6b-, 12,8a-, and 12,8b-olide derivatives of GAA) in nature. Curio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…STLs, which are mainly derived from the precursor germacrene A acid (GAA), are known for their allelopathic effects and are characteristic of the family Asteraceae 19,33,34 . Several enzymes acting downstream of GAA have been elucidated recently, such as HaG8H, LsCOS, and Ih8H, that lead to the formation of different STLs with distinctive stereochemistry [35][36][37] . However, the biosynthetic pathways of STLs in Mikania remain unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…STLs, which are mainly derived from the precursor germacrene A acid (GAA), are known for their allelopathic effects and are characteristic of the family Asteraceae 19,33,34 . Several enzymes acting downstream of GAA have been elucidated recently, such as HaG8H, LsCOS, and Ih8H, that lead to the formation of different STLs with distinctive stereochemistry [35][36][37] . However, the biosynthetic pathways of STLs in Mikania remain unknown.…”
Section: Resultsmentioning
confidence: 99%
“…However, the biosynthetic pathways of STLs in Mikania remain unknown. Lactone ring formation in STLs is dependent upon the (C6 or C8) position and stereoselective hydroxylations of GAA, which can result in STLs with four unique configurations (12, 6α-, 12, 6β-, 12, 8α-, and 12, 8β-olides derivatives of GAA) 37 . Ih8H homolog is important enzyme convert to 7, 8-trans lactone from GAA.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that acid-induced rearrangement may also play a role in plant expression systems and may form rearrangement product combinations with Michael-type adducts [13]. To overcome acid-induced rearrangement in yeast culture, yeast cultures can be buffered [7,39]. The use of MOPS buffer has proven to be better compatible with yeast growth than HEPES buffer [7,39].…”
Section: Acid-induced Rearrangementmentioning
confidence: 99%
“…To overcome acid-induced rearrangement in yeast culture, yeast cultures can be buffered [7,39]. The use of MOPS buffer has proven to be better compatible with yeast growth than HEPES buffer [7,39]. If an acidified HPLC system is necessary, run times can be reduced and when preparative HPLC runs are performed, fractions can be collected in neutral buffer [10,39].…”
Section: Acid-induced Rearrangementmentioning
confidence: 99%
See 1 more Smart Citation